The institutional and economic foundations of regional proto-federations - Emmanouil Marios Lazaros Economou; Nicholas Kyriazis; Theodore Metaxas (European Regional Science Association (ERSA), 2013)
In the present paper we analyse for the first time as far as we know, the ancient Greek regional proto-federations, of free-democratic city-states. We examine their political institutions and policies, like common defense and external policy, military organization, representative federal bodies like popular assemblies, parliament, generals as military and political commanders, federal finance ministers etc., as well as their economic institutions and policies: Common currency, federal budget and federal revenues. We address in more detail as a case study the Aetolian Federation (Greek: Sympolitiae). Lastly, we compare this particular proto-federation with some of today?s federal states and the European Union (EU) and conclude that in some respects the proto-federation was more advanced than the EU, and thus can serve as a benchmark in addressing current European issues. Our main findings indicate that the Aetolian league, in accordance to its regional neighbor, the Achaean League had managed to establish a variety of institutions and mechanisms of governance that secured a satisfactory level of ?balanced? development to its city-state members under a Pareto efficiency perspective. The Aetolian League also achieved an ideal balance between direct and indirect (representative) democracy, an issue that is of major importance for the further EU integration. To achieve this, it established a system of a cumulative sum referendum process which we nominate, ?the Aetolian and Achaean cumulative model of governance?. We argue that this model could offer reliable and stable solutions even in modern EU decision-making processes, when complex issues are difficult to reach in common outcomes. It seems that the Aetolian Confederation had also managed to achieve a perfect combination of a strong institutionalized central government under a democratic profile and attitude. In addition, we argue that the system of monetary policy that comprised by the parallel usage of both local and federal coins that used by the city-state members of the Aetolian Confederation, might be a prodigal example of how to surpass the negative effects of today?s eurocrisis. Finally, we argue that the military organization of the League, could offer some ideas of how to create a would-be Federal Pan-European Armed Forces under the aegis of the EU.
Keywords: D72; H11; H56; H77; N93; R50; 330